Effects of Polygonatum sibiricum Polysaccharides (PSP) on Human Esophageal Squamous Cell Carcinoma (ESCC) via NF-κB Signaling Pathway - Weizheng Zhou; Jiang Hong; Ji Zhu; Xiaowei Wang (International Journal of Polymer Science)
Objective. To explore the effects of different concentrations of Polygonatum sibiricum polysaccharides (PSP) on human esophageal squamous cell carcinoma (ESCC) cell line Eca109 and explore the new approach for the treatment of ESCC. Methods. Eca109 cells were divided into 5 groups, including one control group and 4 experimental groups where the concentrations of PSP used were 50, 100, 200, and 400 μg/mL. The proliferation rate of Eca109 cells in each group was measured with the CCK8 assay, and the apoptosis rate in each group was analyzed by flow cytometry; the in vitro scratch assay was used to determine the migration ability of Eca109 cells after PSP treatment; the expression levels of IL-1, IL-6, IL-10, TNF-α, and TGF-β were measured by RT-PCR, and the expression levels of TLR4 and proteins that are related to NF-κB signaling pathways were determined by Western blot. Results. PSP significantly inhibited the proliferation of Eca109 cells (p<0.05) on a time- and dose-dependent manner; the apoptosis rates of Eca109 cells in experimental groups were significantly increased after 48 h of culture (p<0.05); PSP significantly reduced the migration and invasion ability of Eca109 cells (p<0.05); RT-PCR results showed that the expression of IL-10 in Eca109 cells increased significantly after treatment with PSP (p<0.05), while the expression of IL-1, IL-6, TNF-α, and TGF-β decreased significantly (p<0.05). Compared with the control group, the expression level of TLR4, NF-κB/p50, and NF-κB/p65 protein in each experimental group was significantly lower than that in the control group (p<0.05). Conclusions. PSP significantly inhibited the proliferation, invasion, and migration of Eca109 cells and promoted cell apoptosis. These observed effects were probably due to the PSP’s inhibition on the NF-κB signaling pathway in Eca109 cells via the regulation of the TLR4 expression.